Colorless four-silver low-e glass

By constructing a multi-layer composite film on the surface of the glass substrate, the problem that the glass surface and film surface of high-transmittance four-silver LOW-E glass cannot be colorless at the same time is solved, achieving a balance between colorless effect and high light transmittance, meeting the needs of high-end applications.

CN122254773APending Publication Date: 2026-06-23XINYI GLASS (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610547519.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-23
Publication Date
2026-06-23

Smart Images

  • Figure CN122254773A_ABST
    Figure CN122254773A_ABST
Patent Text Reader

Abstract

The application relates to the field of four-silver coated glass, and particularly discloses a colorless four-silver LOW-E glass, which comprises a glass substrate and a composite film layer deposited on the surface of the glass substrate; the composite film layer is a four-layer silver coating structure formed by compounding SiNx, AZO, NiCr, Ag, ZnAlOx and ZnSnOx in a predetermined order; the thickness of each film layer is accurately controlled; the glass obtained has the following parameters: the glass surface color parameters are Rg=5.7, a*=-0.8 and b*=0.8; the film surface color parameters are Rf=3.9, a*=-1.4 and b*=-0.7; the visible light transmittance T is 67.5%; and the transmittance color parameters are a*=-4.5 and b*=-4.5. The glass surface and the film surface are both colorless, the glass has high light transmittance, and the colorless appearance and the optical transmittance performance are both considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of four-silver coated glass technology, and more specifically, to a colorless four-silver LOW-E glass. Background Technology

[0002] Low-E glass, or low-emissivity coated glass, is widely used in the construction and transportation sectors due to its excellent heat insulation and low emissivity. Among them, quadruple-silver low-E glass, with its multi-layered silver coating, exhibits even better performance in heat insulation and energy saving, thus becoming an important development direction for high-end coated glass.

[0003] Currently, although high-transparency four-silver LOW-E glass has been developed in existing technologies, there are still obvious technical defects. That is, the glass surface and the film surface cannot achieve a colorless effect at the same time. The glass surface or the film surface usually shows a relatively obvious color difference, which makes it difficult to meet the strict requirements for colorless glass appearance in application scenarios such as architectural decoration and high-end manufacturing. This limits the further promotion and application of high-transparency four-silver LOW-E glass in high-end fields.

[0004] Therefore, how to ensure the high light transmittance of four-silver LOW-E glass while achieving a colorless effect on the glass surface, film surface, and transmitted color has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] To overcome the aforementioned deficiencies of the prior art, this invention provides a colorless four-silver LOW-E glass, which is constructed by depositing multiple composite films on the surface of a glass substrate using a coating process to create a four-layer silver-plated structure, and precisely controlling the thickness of each film layer and the optical parameters of the glass. The composite film layer, from the outside in, includes multiple combinations of silicon nitride layer, aluminum-doped zinc oxide layer, nickel-chromium layer, silver layer, zinc-aluminum oxide layer, and zinc-tin oxide layer, as well as an inner silicon nitride layer and a glass substrate. The four silver layers are the core functional layers, the nickel-chromium layer serves as a transition layer for the silver layers, the zinc-aluminum oxide layer and the zinc-tin oxide layer serve as dielectric layers, the silicon nitride layer serves as a protective layer and a base layer, and the aluminum-doped zinc oxide layer serves as a conductive transition layer, thereby solving the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A colorless four-silver LOW-E glass includes a glass substrate and a composite film layer deposited on the surface of the glass substrate. The composite film layer has a four-layer silver-plated structure. By controlling the thickness of each film layer and the overall optical parameters of the glass, the colorless four-silver LOW-E glass can simultaneously have the properties of colorless glass surface, colorless film surface and high light transmittance.

[0008] As a further embodiment of the present invention, the composite film layers, from the side furthest from the glass substrate toward the side of the glass substrate, are sequentially: a first silicon nitride layer (SiNx), a first aluminum-doped zinc oxide layer (AZO), a first nickel-chromium layer (NiCr), a first silver layer (Ag), a first zinc aluminum oxide layer (ZnAlOx), a first zinc tin oxide layer (ZnSnOx), a second aluminum-doped zinc oxide layer (AZO), a second nickel-chromium layer (NiCr), a second silver layer (Ag), a second zinc aluminum oxide layer (ZnAlOx), a second zinc tin oxide layer (ZnSnOx), a third aluminum-doped zinc oxide layer (AZO), a third nickel-chromium layer (NiCr), a third silver layer (Ag), a third zinc aluminum oxide layer (ZnAlOx), a third zinc tin oxide layer (ZnSnOx), a fourth aluminum-doped zinc oxide layer (AZO), a fourth nickel-chromium layer (NiCr), a fourth silver layer (Ag), a fourth zinc aluminum oxide layer (ZnAlOx), a second silicon nitride layer (SiNx), and the glass substrate.

[0009] As a further aspect of the present invention, the thickness of each film layer is controlled as follows:

[0010] The thickness of the first silicon nitride layer is 25-30 nm;

[0011] The thickness of the first to fourth aluminum-doped zinc oxide layers is 10-15 nm.

[0012] The thickness of the first to fourth nickel-chromium layers is 0.5 nm.

[0013] The thicknesses of the first to fourth silver layers are 14-15 nm, 12.5-13.5 nm, 10-11 nm, and 8-9 nm, respectively.

[0014] The thickness of the first to third zinc-aluminum oxide layers is 15-20 nm, and the thickness of the fourth zinc-aluminum oxide layer is 10-15 nm.

[0015] The thickness of the first zinc tin oxide layer is 60-65 nm, and the thickness of the second and third zinc tin oxide layers is 55-60 nm.

[0016] The thickness of the second silicon nitride layer is 15-20 nm.

[0017] Among them, the nickel-chromium layer serves as a transition layer for the silver layer, the zinc-aluminum oxide layer and the zinc-tin oxide layer serve as dielectric layers, the silicon nitride layer serves as a protective layer and a substrate layer, the aluminum-doped zinc oxide layer serves as a conductive transition layer, and the four silver layers serve as the core functional layers. Through precise control of the thickness and structural matching of each film layer, the overall optical performance of the glass is optimized.

[0018] As a further aspect of the present invention, the optical color parameters and transmittance indices of the glass surface, film surface, and transmitted light of the colorless four-silver LOW-E glass are as follows: the glass surface color parameters are Rg=5.7, a*=-0.8, b*=0.8; the film surface color parameters are Rf=3.9, a*=-1.4, b*=-0.7; the visible light transmittance T is 67.5%; and the transmitted color parameters are a*=-4.5, b*=-4.5.

[0019] The technical effects and advantages of this invention's colorless four-silver LOW-E glass are as follows: This invention achieves colorless glass and film surfaces, meeting the requirements of applications demanding colorless glass appearance; while achieving colorless glass, film surfaces, and transmitted light, the visible light transmittance still reaches 67.5%, balancing colorless appearance with high light transmittance, solving the problem of difficulty in achieving both colorlessness and high transmittance in existing technologies; through a gradient thickness design of four silver layers, combined with a nickel-chromium transition layer, a zinc aluminum oxide / zinc tin oxide dielectric layer, an AZO conductive transition layer, and a SiNx protective layer to form a composite film structure, this invention optimizes optical performance while ensuring the bonding stability between the film and the glass substrate, and retains the original heat insulation and low-emissivity properties of the four-silver LOW-E glass. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the structure of a colorless four-silver LOW-E glass according to the present invention. Detailed Implementation

[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1

[0023] like Figure 1 As shown, this invention discloses a colorless four-silver LOW-E glass, comprising a glass substrate and a composite film layer deposited on the surface of the glass substrate. The composite film layer is disposed on the surface of the glass substrate and, together with the glass substrate, constitutes the overall structure of the colorless four-silver LOW-E glass. The composite film layer is a four-layer silver-plated structure, formed by sequentially stacking multiple layers of film and deposited on the surface of the glass substrate using a magnetron sputtering process. This film layer construction method enables the composite film layer to form a stable multilayer film structure on the surface of the glass substrate, providing a foundation for achieving the overall optical performance of the glass.

[0024] Specifically, the composite film layers, from the side furthest from the glass substrate towards the side facing the glass substrate, are sequentially arranged as follows: a first silicon nitride layer, a first aluminum-doped zinc oxide layer, a first nickel-chromium layer, a first silver layer, a first zinc-aluminum oxide layer, a first zinc-tin oxide layer, a second aluminum-doped zinc oxide layer, a second nickel-chromium layer, a second silver layer, a second zinc-aluminum oxide layer, a second zinc-tin oxide layer, a third aluminum-doped zinc oxide layer, a third nickel-chromium layer, a third silver layer, a third zinc-aluminum oxide layer, a third zinc-tin oxide layer, a fourth aluminum-doped zinc oxide layer, a fourth nickel-chromium layer, a fourth silver layer, a fourth zinc-aluminum oxide layer, a second silicon nitride layer, and the glass substrate. These layers are arranged sequentially and stacked in a predetermined order to form a complete four-silver composite film layer structure. The four silver layers constitute the core functional layers of the composite film layer, with the remaining layers arranged around them to coordinate and match the overall performance of the glass.

[0025] The composite film has the following characteristics: the first silicon nitride layer has a thickness of 25-30 nm, the second silicon nitride layer has a thickness of 15-20 nm, the first to fourth aluminum-doped zinc oxide layers each have a thickness of 10-15 nm, the first to fourth nickel-chromium layers each have a thickness of 0.5 nm, the first to fourth silver layers have thicknesses of 14-15 nm, 12.5-13.5 nm, 10-11 nm, and 8-9 nm respectively, the first to third zinc-aluminum oxide layers each have a thickness of 15-20 nm, the fourth zinc-aluminum oxide layer has a thickness of 10-15 nm, the first zinc-tin oxide layer has a thickness of 60-65 nm, and the second and third zinc-tin oxide layers each have a thickness of 55-60 nm. Therefore, the composite film layers not only have a clear hierarchical arrangement but also corresponding parameter control ranges for the thickness of each layer. By controlling the thickness of each layer, a cooperative relationship is formed between the layers in the overall structure, thus providing a foundation for the colorless four-silver LOW-E glass to achieve its intended optical performance.

[0026] In the aforementioned composite film layer, the layers are closely stacked, with adjacent layers sequentially connected to form a continuous film system. Specifically, a nickel-chromium layer serves as a transition layer between the silver layers and the aluminum-doped zinc oxide layer, forming a transition structure that complements the silver layers. Zinc-aluminum oxide and zinc-tin oxide layers serve as dielectric layers, positioned between the silver layers and between adjacent layers to form a dielectric structure corresponding to the multilayer silver film. A silicon nitride layer serves as both a protective layer and a substrate layer, positioned on the outer side of the composite film layer and the side closest to the glass substrate, respectively. An aluminum-doped zinc oxide layer serves as a conductive transition layer, complementing the nickel-chromium layer and related functional layers. Four silver layers form the core functional layers, arranged in the composite film layer in the aforementioned order. By precisely controlling the thickness of each layer and matching the structural relationships between them, the entire composite film layer forms an orderly, continuous, and mutually complementary multilayer structure, optimizing the overall optical performance of the glass.

[0027] Furthermore, in terms of film thickness distribution, the thicknesses of the first to fourth silver layers are 14-15 nm, 12.5-13.5 nm, 10-11 nm, and 8-9 nm, respectively, exhibiting a structural characteristic of gradual variation along the film layer arrangement direction; the thicknesses of the first to third zinc-aluminum oxide layers are all 15-20 nm, and the thickness of the fourth zinc-aluminum oxide layer is 10-15 nm; the thickness of the first zinc-tin oxide layer is 60-65 nm, and the thicknesses of the second and third zinc-tin oxide layers are both 55-60 nm. These film thickness settings correspond to the layer order of the composite film layers, collectively constituting the film system structure of the colorless four-silver LOW-E glass. Through the corresponding combination of the above structural order and film thickness range, a complete four-silver LOW-E film layer system is formed on the surface of the glass substrate.

[0028] The colorless four-silver LOW-E glass obtained in this embodiment has the following surface color parameters: Rg=5.7, a*=-0.8, b*=0.8; film surface color parameters: Rf=3.9, a*=-1.4, b*=-0.7; visible light transmittance T: 67.5%; and transmitted color parameters: a*=-4.5, b*=-4.5. As can be seen from the above parameters, the glass obtained in this embodiment achieves a colorless effect in terms of surface color, film surface color, and transmitted color, while maintaining a high level of visible light transmittance. In other words, under the combined effect of the composite film structure, the film layer arrangement order, and the thickness range of each layer, this invention can achieve a colorless effect on the surface, film surface, and transmitted color while maintaining high light transmittance, thereby solving the problem that existing high-transmittance four-silver LOW-E glass cannot simultaneously achieve colorlessness on both the surface and film surface.

[0029] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

[0030] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A colorless tetrasilver LOW-E glass, comprising a glass substrate and a composite film layer deposited on the surface of the glass substrate, characterized in that, The composite film layer has a four-layer silver-plated structure. The composite film layer, from the side away from the glass substrate towards the side of the glass substrate, sequentially includes a first silicon nitride layer, a first aluminum-doped zinc oxide layer, a first nickel-chromium layer, a first silver layer, a first zinc-aluminum oxide layer, a first zinc-tin oxide layer, a second aluminum-doped zinc oxide layer, a second nickel-chromium layer, a second silver layer, a second zinc-aluminum oxide layer, a second zinc-tin oxide layer, a third aluminum-doped zinc oxide layer, a third nickel-chromium layer, a third silver layer, a third zinc-aluminum oxide layer, a third zinc-tin oxide layer, a fourth aluminum-doped zinc oxide layer, a fourth nickel-chromium layer, a fourth silver layer, a fourth zinc-aluminum oxide layer, and a second silicon nitride layer.

2. The colorless tetrasilver LOW-E glass according to claim 1, characterized in that... The thickness of the first silicon nitride layer is 25-30 nm, the thickness of the second silicon nitride layer is 15-20 nm, the thickness of the first to fourth aluminum-doped zinc oxide layers is 10-15 nm, the thickness of the first to fourth nickel-chromium layers is 0.5 nm, the thickness of the first to fourth silver layers is 14-15 nm, 12.5-13.5 nm, 10-11 nm and 8-9 nm respectively, the thickness of the first to third zinc-aluminum oxide layers is 15-20 nm, the thickness of the fourth zinc-aluminum oxide layer is 10-15 nm, the thickness of the first zinc-tin oxide layer is 60-65 nm, and the thickness of the second and third zinc-tin oxide layers is 55-60 nm.

3. The colorless tetrasilver LOW-E glass according to claim 2, characterized in that... The composite film layer is deposited on the surface of the glass substrate using a magnetron sputtering process.

4. The colorless tetrasilver LOW-E glass according to claim 1, characterized in that, The glass surface and the film surface of the colorless four-silver LOW-E glass are both colorless.

5. The colorless tetrasilver LOW-E glass according to claim 1, characterized in that, The colorless four-silver LOW-E glass described above has a colorless transmittance.

6. The colorless tetrasilver LOW-E glass according to claim 1, characterized in that, The colorless four-silver LOW-E glass has the following surface color parameters: Rg=5.7, a*=-0.8, b*=0.8; film surface color parameters: Rf=3.9, a*=-1.4, b*=-0.7; visible light transmittance T: 67.5%; and transmittance color parameters: a*=-4.5, b*=-4.

5.

7. The colorless tetrasilver LOW-E glass according to claim 1, characterized in that, The thickness of the first silver layer, the second silver layer, the third silver layer, and the fourth silver layer decreases sequentially from the side away from the glass substrate toward the side of the glass substrate.

8. The colorless tetrasilver LOW-E glass according to claim 1, characterized in that, The thickness of the first zinc-tin oxide layer is greater than that of the second and third zinc-tin oxide layers, and the thickness of the first, second, and third zinc-aluminum oxide layers is greater than that of the fourth zinc-aluminum oxide layer.